Utility of Repeat Nasopharyngeal SARS-CoV-2 RT-PCR Testing and Refinement of Diagnostic Stewardship Strategies at a Tertiary Care Academic Center in a Low-Prevalence Area of the United States - Lepak, Alexander J (Open Forum Infect Dis, 2020)
BACKGROUND: Multiple factors have led to an extremely high volume of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) reverse transcription polymerase chain reaction (RT-PCR) testing. Concerns exist about sensitivity and false-negative SARS-CoV-2 RT-PCR testing results. We describe a retrospective observational study examining the utility of repeat nasopharyngeal (NP) SARS-CoV-2 RT-PCR testing at an academic center in a low-prevalence setting. METHODS: All patients within our health system with >1 NP SARS-CoV-2 RT-PCR test result were included. SARS-CoV-2 RT-PCR testing was performed according to 1 of 4 validated assays. Key clinical and demographic data were collected, including whether the patient was inpatient or outpatient at time of the test and whether the test was performed as part of a person under investigation (PUI) for possible coronavirus disease 2019 or for asymptomatic screening. RESULTS: A total of 660 patients had >1 NP SARS-CoV-2 PCR test performed. The initial test was negative in 638. There were only 6 negative-to-positive conversions (0.9%). All 6 were outpatients undergoing a PUI workup 5–17 days after an initial negative result. In >260 inpatients with repeat testing, we found no instances of negative-to-positive conversion including those undergoing PUI or asymptomatic evaluation. CONCLUSIONS: In a low-prevalence area, repeat inpatient testing after an initial negative result, using a highly analytically sensitive SARS-CoV-2 RT-PCR, failed to demonstrate negative-to-positive conversion. The clinical sensitivity of NP RT-PCR testing may be higher than previously believed. These results have helped shape diagnostic stewardship guidelines, in particular guidance to decrease repeated testing in the inpatient setting to optimize test utilization and preserve resources.